Infusion of Hematopoietic Stem Cells: Types, Characteristics, Adverse and Transfusion Reactions and the Implications for Nursing Infusión de células madre hematopoyéticas: tipos, características, reacciones adversas y de transfusión y sus implicaciones para la enfermería Infusão de células-tronco hematopoéticas: tipos, características, reações adversas e transfusionais e implicações para a enfermagem - Ana Carolina de Jesus Vieira Curcioli; Emilia Campos de Carvalho (Universidade de São Paulo, 2010)
Hematopoietic stem cell infusion is an important procedure in Hematopoietic Stem Cell Transplantation (HSCT). This study identifies transfusion and other adverse reactions that can occur during infusion and the nursing care related to the procedure. This epidemiologic study used transplantations performed between 2006 and 2008. A total of 166 transplantations were performed: 114 were autologous, 47 allogeneic and five haploidentical. Three transfusion reactions and 96 adverse reactions were observed. Adverse reactions were related to the presence of cryoprotectant, though the infusion rate and quantity of infused cryoprotectant were not related to the occurrence of reactions. The products were fresh and infused within the recommended time when transfusion reactions occurred. In regard to cell source, lower engraftment time was found in peripheral blood. Nursing documentation is relevant for patients' safety as well to planning an infusion in order to minimize the occurrence of reactions. La infusión de las células madre hematopoyéticas es un importante procedimiento en el trasplante de células madre hematopoyéticas. Este estudio se propuso identificar las reacciones adversas y de transfusión que pueden ocurrir durante la infusión y los cuidados de enfermería inherentes al procedimiento. Se trata de un estudio epidemiológico en trasplantes ocurridos en los años de 2006 a 2008. En ese período ocurrieron 166 trasplantes, siendo 114 autólogos, 47 alogénicos y 5 haploidénticos. Se observaron tres reacciones de transfusión y 96 reacciones adversas. Las reacciones adversas están ligadas a presencia del crioprotector. Sin embargo, la velocidad de infusión y la cantidad del crioprotector infundido, no tuvieron relación con la ocurrencia de las reacciones. En las reacciones de transfusión, los productos eran frescos e infundidos con la velocidad preconizada. En cuanto a las fuentes de células, hubo menor tiempo de injerto en la sangre periférica. La documentación de enfermería es relevante tanto para la seguridad del paciente como para la planificación de la infusión, a fin de minimizar la ocurrencia de las reacciones. A infusão de células-tronco hematopoéticas é importante procedimento no transplante de células-tronco hematopoéticas. Este estudo se propôs a identificar as reações adversas e transfusionais que podem ocorrer durante a infusão e os cuidados de enfermagem inerentes ao procedimento. Trata-se de estudo epidemiológico em transplantes, ocorridos entre os anos 2006 e 2008. Ocorreram 166 transplantes, sendo 114 autólogos, 47 alogênicos e 5 haploidênticos. Observaram-se três reações transfusionais e 96 reações adversas. As reações adversas estão ligadas à presença do crioprotetor. No entanto, velocidade de infusão e quantidade do crioprotetor infundido não tiveram relação com a ocorrência das reações. Nas reações transfusionais, os produtos eram frescos e infundidos na velocidade preconizada. Quanto às fontes de células, houve menor tempo de enxertia no sangue periférico. A documentação de enfermagem é relevante tanto para a segurança do paciente como para o planejamento da infusão, a fim de minimizar a ocorrência das reações.